A case report of cardiac neuromodulation in a young patient with a third-degree atrioventricular block - Noemi Valenti; Antonio Di Monaco; Imma Romanazzi; Nicola Vitulano; Federica Troisi; Federico Quadrini; Massimo Grimaldi (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThere are some functional bradyarrhythmias that are caused by a dysregulation of the autonomic nervous system, for which a therapeutic strategy of cardioneuroablation (CNA) is conceivable.Case summaryIn this study, we report the case of a 19-year-old woman with a non-congenital third-degree atrioventricular block (AVB), symptomatic for lipothymia and dyspnea caused by mild exertion. She had a structurally normal heart and no other comorbidities. The atropine test and the exercise stress test documented a sinus tachycardia at 190 bpm with a 2:1 AVB, a narrow QRS, and an atrioventricular conduction of 1:1 until reaching a sinus rhythm rate of 90 bpm. She underwent the CNA procedure, which targeted the inferior paraseptal ganglion plexus, with a gradual change in the ECG levels recorded during the radiofrequency delivery from a third-degree AVB to a first-degree AVB. After the procedure, we observed a complete regression of the third-degree AVB, with evidence of only a first-degree AVB and a complete regression of symptoms until the 6-month follow-up.ConclusionsAlthough not yet included in current guidelines, the CNA procedure could be used to treat AV node dysfunction in young subjects, as it could represent an alternative to pacemaker implantation. However, more randomized studies are needed to assess the long-term efficacy of this promising technique.